Perspectivas da digestão anaeróbia na produção de biogás a partir de resíduos orgânicos: uma análise sistemática da literatura - Sacoman, Diego Angelo (Universidade Federal de São Carlos, 2024)
Anaerobic digestion of waste is a research topic that has gained increasing relevance due to its relationship with the topic of sustainability, in the context of the need to deal with organic waste, mainly industrial, which in several countries is discarded in exorbitant quantities causing drastic environmental pollution, in addition to the alternative relying on the production of biogas, especially methane, and bioenergy. Therefore, this work aims to carry out a bibliographical analysis and systematic review of the literature, exploring the concepts of anaerobic digestion and anaerobic co-digestion, the relationship with heterogeneous substrates and their efficiencies. Furthermore, the literature review also analyzes scientific publications on the subject of anaerobic treatment of organic waste, verifying different approaches, observing the most relevant parameters for the treatment and production of biogas. For detailed analysis of scientific studies, the Scopus and Web of Science database will be used. Based on the data presented, we intend to analyze the main topics of study and, highlighting the most cataloged substrates, countries and periods with the largest publications, and conclude whether anaerobic co-digestion is a promising strategy for the treatment of organic waste, to minimize the environmental impact.
Perspectives of anaerobic digestion in biogas production from organic wastes: a systematic literature review
Keywords: Digestão anaeróbia; Co-digestão anaeróbia; Tratamento de resíduos orgânicos; Biogás; Sustentabilidade; Anaerobic digestion; Anaerobic co-digestion; Organic waste treatment; Biogas; Sustainability; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA